Metamaterial-inspired microfluidic-based sensor for chemical discrimination - Jaruwongrungsee, Kata; Withayachumnankul, Withawat; Wisitsoraat, Anurat; Abbott, Derek; Fumeaux, Christophe; Tuantranont, Adisorn (My University, 2012)
This work proposes a metamaterial-inspired microfluidic-based chemical sensor. The sensor comprises a microwave split-ring resonator (SRR), an important building block of metamaterials, integrated with a disposable flow-channel made of a transparency film. The electromagnetic response of the sensor is observed in the presence of various analytes including glycerol, ethanol, and phosphate buffered saline. It is found that the resonance frequency in the transmission amplitude and the zero crossing in the reflection phase of the sensor are good features for discrimination of these analytes and for determining their concentrations. The developed metamaterial-inspired microfluidic-based chemical sensor has a potential for advanced chemical sensing applications. © 2012 IEEE.